Optimising performance of a confocal fluorescence microscope with a differential pinhole - Kakade, Rohan; Walker, John G.; Phillips, Andrew J. (IOP Publishing, 2015)
The signal-to-noise ratio (SNR)-resolution trade-off is of great importance to bio-imaging applications where the aim is to image the sample using as little light as possible without significantly sacrificing image quality. In this paper the inherent SNR-resolution tradeoff in Confocal Fluorescence Microscopy (CFM) systems is presented by means of an effective tradeoff curve. A CFM system that employs a differential pinhole detection scheme has recently been shown to offer increased resolution, but at the expense of SNR. An optimum profile for the differential pinhole is identified in this paper that offers improved performance over a conventional (circular pinhole) system. The performance enhancement is illustrated through computer simulation.